Pregnancy Patterns Impact Live Birth Rate for Patients With Intrauterine Adhesions After Hysteroscopic Adhesiolysis: A Retrospective Cohort Study - Sun, Dan; Mao, Xuetao; Zhang, Aiqian; Gao, Bingsi; Huang, Huan; Burjoo, Arvind; Xu, Dabao; Zhao, Xingping (Frontiers in Physiology, 2022)
Objective: The pregnancy patterns and other factors of live birth for patients with intrauterine adhesions (IUAs) were identified by analyzing the clinical features of pre-, intra-, and posthysteroscopic adhesiolysis (HA). Design: A total of 742 patients with IUAs who wanted to become pregnant underwent HA from January 2017 to May 2018 at the Third Xiangya Hospital of Central South University. The patient follow-up period was 2 years post-HA. A logistic regression was performed to analyze the clinical characteristics associated with a live birth for patients with IUAs. Preoperative clinical indicators included age, gravidity, parity, abortion, IUA recurrence, menstrual patterns, disease course. Intraoperative clinical features assessed in the last operation were uterine cavity length, IUA appearance, IUA area, number of visible uterine cornua, number of visible tubal ostia, AFS scores. Pregnancy patterns were posthysteroscopic adhesiolysis features. Results: Among the 742 IUA patients, 348 (46.9%) had a live birth and 394 (53.1%) did not. A bivariate and binary logistic regression analysis showed that IUA patients’ pregnancy patterns, age, number of visible tubal ostia noted by a second-look hysteroscopy, and American Fertility Society (AFS) scores were significantly related to the live birth rate (P <.05). Conclusions: Pregnancy patterns, age, number of visible tubal ostia, and AFS scores were significantly related to the live birth rate and may be considered potential predictors of the live birth rate in IUA patients. The indications of assisted reproductive technology (ART) might be a better choice for patients with recurrent IUAs.